Repeated sprint ability in young basketball players: one vs. two changes of direction (Part 2) - Attene, G.; Laffaye, G.; Chaouachi, A.; Pizzolato, F.; Migliaccio, G.; Padulo, J. (Journal of Sports Sciences, 2015)
The aim of this study was to compare the training effects based on repeated sprint ability (RSA) (with one change of direction) with an intensive repeated sprint ability (IRSA) (with two changes of direction) on jump performance and aerobic fitness. Eighteen male basketball players were assigned to repeated sprint ability and intensive repeated sprint ability training groups (RSAG and IRSAG). RSA, IRSA, squat jump (SJ), countermovement jump (CMJ) and Yo-Yo intermittent recovery level 1 test were assessed before and after four training weeks. The RSA and IRSA trainings consisted of three sets of six sprints (first two weeks) and eight sprints (second two weeks) with 4-min sets recovery and 20-s of sprints recovery. Four weeks of training led to an overall improvement in most of the measures of RSA, but little evidence of any differences between the two training modes. Jump performance was enhanced: CMJ of 7.5% (P < 0.0001) and 3.1% (P = 0.016) in IRSAG and RSAG respectively. While SJ improved of 5.3% (P = 0.003) for IRSAG and 3.4% (P = 0.095) for RSAG. Conversely the Yo-Yo distance increased 21% (P = 0.301) and 34% (P = 0.017) in IRSAG and RSAG respectively. Therefore, short-term repeated sprint training with one/two changes of direction promotes improvements in both RSA and IRSA respectively but the better increase on jump performance shown a few changes on sprint and endurance performances.